Giải và biện luận HPT: $\left \{ {{(m-2)x + my = 2m} \atop {(m+1)x – my = m+1}} \right.$

Question

Giải và biện luận HPT:
$\left \{ {{(m-2)x + my = 2m} \atop {(m+1)x – my = m+1}} \right.$

in progress 0
Ariana 2 tháng 2021-10-13T02:22:42+00:00 1 Answers 5 views 0

Answers ( )

    0
    2021-10-13T02:23:53+00:00

    Đáp án:

    $\begin{array}{l}
    \left\{ \begin{array}{l}
    \left( {m – 2} \right).x + my = 2m\\
    \left( {m + 1} \right).x – my = m + 1
    \end{array} \right.\\
     \Rightarrow \left( {m – 2} \right).x + \left( {m + 1} \right).x = 2m + m + 1\\
     \Rightarrow \left( {2m – 1} \right).x = 3m + 1\\
     + Khi:2m – 1 = 0 \Rightarrow m = \dfrac{1}{2}\\
     \Rightarrow 0.x = \dfrac{5}{2}
    \end{array}$

    => Hệ pt vô nghiệm

    $\begin{array}{l}
     + Khi:m \ne \dfrac{1}{2} \Rightarrow x = \dfrac{{3m + 1}}{{2m – 1}}\\
     \Rightarrow \left( {m – 2} \right).x + my = 2m\\
     \Rightarrow my = 2m – \left( {m – 2} \right).x\\
     \Rightarrow m.y = 2m – \left( {m – 2} \right).\dfrac{{3m + 1}}{{2m – 1}}\\
     \Rightarrow m.y = \dfrac{{4{m^2} – 2m – 3{m^2} + 5m + 2}}{{2m – 1}}\\
     \Rightarrow y = \dfrac{{{m^2} + 3m + 2}}{{m\left( {2m – 1} \right)}}\\
     \Rightarrow \text{pt có nghiệm duy nhất}:x = \dfrac{{3m + 1}}{{2m – 1}};y = \dfrac{{{m^2} + 3m + 2}}{{m\left( {2m – 1} \right)}}\\
    Khi:m \ne \dfrac{1}{2};m \ne 0
    \end{array}$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )